(untitled) (The South East European Journal of Economics and Business, 2024)
A stock market plays a pivotal role in a financial system and is monitored as a yardstick of a healthy economy. It is a stylized fact that there is a positive and significant relationship between financial development and economic growth. However, emerging markets often exhibit more volatile returns than developed markets, and extreme volatility might prevent financial stability. The literature underlines the role of uncertainty in predicting volatility and suggests a strong positive association between economic policy uncertainty and stock market volatility. Against this backdrop, this study examines the dynamic nature of relationships between economic policy uncertainty (in Germany and the US) and long-run stock market volatility of CEE-3 (Central and Eastern European: the Czech Republic, Hungary, and Poland) countries. This study follows two steps in empirical analysis. First, it obtains long-run stock market volatility and then estimates dynamic regression models. The evidence shows a positive and significant one-period lagged impact of economic policy uncertainty on long-run stock market volatility.